Problems of Using Innovative Learning Media in the Digitalization Era of the Merdeka Program in Basic Education - Mariati, Pance; Anlianna; Sakbana Kusuma, Rendra; Sunanto; Suryanti; Wiryanto (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
The purpose of this study is to describe the problems of using digital-based innovative learning media in the digitalization era which is an independent learning program in basic education. This problem is very important to study more deeply, considering that learning media is an important component that must exist in the implementation of learning. The method used in this research is descriptive qualitative. The research was conducted at SDN Sidosermo 1 Surabaya during December 2022. The data needed in this study included literature studies, direct observation, supported by questionnaire results and interviews with PPG students who carried out PPL at SDN Sidosermo 1 Surabaya. The results of this study note that there are still teachers who have not utilized digital-based innovative learning media during learning. Teachers still use the lecture method and simple media in the form of pictures and word cards to support learning. The lack of use of digital-based innovative learning media is not only seen in Sidosermo 1 Surabaya Elementary School, but also in several schools in Indonesia. This is known from data which states that around 60% of teachers in Indonesia still do not master information and communication technology. Based on the results of this study it can be concluded that the use of digital-based innovative learning media is still minimal and needs to be improved in the future. It is intended that there is a balance between technological advances and scientific advances in the school environment, which in turn can improve the quality of learning